Brain metastases from germ cell tumor: time to reconsider radiotherapy?. (June 2020) - Khalifa, Jonathan; Fléchon, Aude; Chevreau, Christine
Graphical abstract: Highlights: The presence of brain metastases (BMs) from germ cell tumor is a rare and challenging clinical scenario. Synchronous BMs are almost systematically associated with extra-cerebral metastases. The role of local treatment for synchronous BMs is controversial. Metachronous BMs are associated with poorer outcome and local treatment is more consensual. The concept of radioresistance for non-seminomatous tumors should be reexamined at the era of stereotactic radiotherapy. Abstract: The presence of brain metastases (BMs) from germ cell tumor (GCT) remains a rare situation. BMs predominantly occur among patients with testis primary tumor site, and are almost exclusively associated with non-seminomatous (NS) histologies. Two situations must be distinguished, which differ in terms of clinical presentation, overall prognostic and management. At diagnosis, BMs are almost systematically associated with extra-cerebral metastases and the cornerstone of treatment is chemotherapy, while the role of local treatment remains controversial. In the metachronous setting, BMs more frequently constitute an isolated site of relapse, the outcome is poorer, and the role of local treatment is more consensual. However, all these data widely come from old reports, with outdated radiation techniques. The recent advances in radiation oncology, especially the rising use of stereotactic radiotherapy, could lead to the reconsideration of ancient dogmas regarding the "radiosensitivity" of (NS)GCT and the role of radiotherapy among patients with BMs.